War owl falling : innovation, creativity, and culture change in ancient Maya society - Eberl, Markus (Maya studies., 2017)
Unlike earlier geometric decorations, the war owls and other eighth-century motifs relate to Classic Maya art and writing. Eberl probes their meaning by comparing where they occur and by situating them in social structures that circumscribe individual action.